The Chinese adaptation of the mathematical resilience scale among high school students: Validity and reliability study - Meirong, Zhang; Mustafa, Zaida (Edelweiss Applied Science and Technology, 2025)
Mathematical resilience (MR) is a critical learning attitude that enables students to overcome challenges in mathematics. However, there is a lack of validated instruments to assess MR in Chinese high schools. This study aimed to adapt the internationally developed Mathematical Resilience Scale (MRS) for Chinese high school students and evaluate its reliability and validity. Using a quantitative research design, the study conducted three rounds of confirmatory factor analysis (CFA) to examine the three-factor structure (value, struggle, and growth). The first two rounds revealed low correlations between factors and weak loadings on resilience. After eliminating translation issues, removing items (V7, S5), and adapting the reverse-scored items to make them positively scored, the study demonstrated good structural, discriminant, and convergent validity. The Cronbach’s alpha coefficients were 0.891 (value), 0.892 (struggle), 0.910 (growth), and 0.927 (overall scale), while McDonald’s omega values were 0.891 (value), 0.890 (struggle), 0.909 (growth), and 0.922 (overall scale). These findings indicate that the adapted MRS is a reliable and valid tool for assessing MR among Chinese high school students. This study provides a practical instrument for educators to identify and support students with low MR, ultimately enhancing their mathematical learning outcomes and reducing math anxiety.